An electro-thermal micro-actuator based on polymer composite for application to dual-stage positioning systems of hard disk drives - Yang, J. P. (2013)
This paper presents an electro-thermal micro-actuator based on polymer composite for dual-stage head positioning systems in hard disk drives (HDDs). This micro-actuator has a pair of benders, which are made of silicon–polymer composite. When electro-thermally activated by resistive heating, the composite expands and consequently the benders produce a lateral bending motion to drive a femto slider, which carries a magnetic read/write head. The micro-actuator has been fabricated by deep silicon etching and polymer patterning. Experiment shows that the micro-actuator can drive up to 35 nm peak-to-peak displacement when it is activated by a 3.25 V half-sine input voltage at 500 Hz under a moderate temperature rise. The first in-plane mechanical resonant frequency is measured to occur at 36.8 kHz. Analytical and finite element models were developed to simulate the micro-actuator performance. It is noted that the simulation results agree well with the experimental measurement. With good performance, the electro-thermal micro-actuator are useful for high bandwidth dual-stage positioning systems in future high-density HDDs.